MODEL PENDIDIKAN ISLAM NUSANTARA - Inayah Inayah (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2021)
The development of Islamic education in Indonesia, among others, is marked by the gradual emergence of various educational institutions, ranging from very simple ones, to stages that are considered modern and complete. The research method in this article is qualitative with library research. Literature research through library research based on literature. This study aims to photograph the model of Islamic education in the archipelago. The results of this study indicate that changes in Islamic educational institutions, both classical and modern; starting from homes, mosques, Islamic boarding schools, schools to boarding schools and Islamic universities is a metamorphosis of Islamic educational institutions in the archipelago.